Measurements of the associated production of a W boson and a charm quark in proton-proton collisions at √s=8TeV - Tumasyan,A; Adam,W; Bergauer,T; Dragicevic,M; Ero,J; Del,Valle AE; Fruhwirth,R; Jeitler,M; Krammer,N; Lechner,L; Liko,D; Madlener,T; et al. (European Physical Journal C: Particles and Fields, 2022)
Measurements of the associated production of aW boson and a charm (c) quark in proton–proton collisionsat a centre-of-mass energy of 8 TeV are reported. The analysis uses a data sample corresponding to a total integratedluminosity of 19.7 fb−1 collected by the CMS detector atthe LHC. The W bosons are identified through their leptonicdecays to an electron or a muon, and a neutrino. Charm quarkjets are selected using distinctive signatures of charm hadrondecays. The product of the cross section and branching fraction σ (pp → W + c + X)B(W → ν), where = e or μ,and the cross section ratio σ (pp → W+ + ¯c + X)/σ (pp →W− + c + X) are measured in a fiducial volume and differentially as functions of the pseudorapidity and of the transverse momentum of the lepton from the W boson decay. Theresults are compared with theoretical predictions. The impactof these measurements on the determination of the strangequark distribution is assessed.